The Changes of Interleukin 17 levels On Pulmonary Tuberculosis Patients with AFB Smear-Positive After 2 Months Anti Tuberculosis Drugs Treatment - Andy Sulaiman Siregar; Soedarsono Soedarsono (Jurnal Respirologi Indonesia, 2018)
Background: Tuberculosis still remain as a health problem in the world. No specific biomarkers can be used to monitor the rapid response to TB therapy. This study aims to assess the change of IL-17 levels in pulmonary tuberculosis patients with AFB smear-positive before and after 2 months of anti tuberculosis drugs (ATD) treatment. Method: Design of study is analytic observational with prospective cohort. The subject include 17 new cases of pulmonary tuberculosis patients with AFB smear-positive in Soetomo Hospital Surabaya from July - October 2016. Plasma levels of IL-17 were measured using ELISA technique before treatment and 2 months after the ATD therapy. Results: The mean levels of IL-17 before treatment is 3.510 pg / ml (2.087- 5.051 pg/ml). There were significantly decreament (p = 0.001